Evolution of the charge carrier plasmon in the one-dimensional metal TTF-TCNQ as a function of temperature and momentum. (11th September 2019) - Kovbasa, Nikolay; Graf, Lukas; Knupfer, Martin
Abstract: We have investigated the charge carrier plasmon in the quasi one-dimensional metal TTF-TCNQ using electron energy-loss spectroscopy. Our data reveal a negative plasmon dispersion with a slope that is independent of temperature, which is in agreement to predictions from model calculations and previous room temperature data. A plasmon energy shift upon temperature is observed, and we discuss possible contributions to this shift. The spectral width of the plasmon is rather temperature independent, but increases clearly above a momentum value of about 0.3 Å −1 .